(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the challenges and strategies involved in translating metaphorical phrases in political texts from English to Uzbek and vice versa. Through a comparative analysis, it investigates how cultural nuances, linguistic differences, and socio-political contexts influence the translation process. The study employs various methods to examine the effectiveness of different translation techniques, aiming to enhance cross-cultural understanding and improve the quality of political translations.